FAKTOR FAKTOR YANG MEMPENGARUHI TERJADINYA IKTERUS PADA NEONATUS DI RSKDIA SITI FATIMAH MAKASSAR - Bahar, Ika Nurfitri (Jurnal Martenity and Neonatal, 2017)
The incidence of jaundice is a problem in newborns, occurs in approximately 25-50% of term infants and higher in preterm infants. The purpose of this study to determine whether gestational age, birth weight infants and types of labor are factors that influence the occurrence of jaundice in neonates in RSKDIA Sitti Fatimah Makassar 2014.This type of research used in this research is descriptive research analytic cohort approach retrosfektif and a sample of 102 is composed of 51 samples of infants with jaundice and 51 samples of infants who are not jaundiced obtained from secondary data. Data presented in the form of univariate and bivariate with chi square test to determine the factors of fariabel through SPSS 17.0.The results using the chi square test found no effect of gestation (p value = 0.000), birth weight (p value = 0.000) and the type of delivery (p value = 0.000) in the incidence of neonatal jaundice in RSKDIA Sitti Fatimah Makassar 2015.The results of this study concluded that there was the influence of gestational age, birth weight, and type of labor on the incidence of neonatal jaundice. It is expected to improve the delivery of health care workers for counseling on the factors that influence the occurrence of neonatal ikerus and conduct health promotion efforts on a variety of health problems, including neonatal jaundice which is one of the causes of infant mortality.